Estudos dos fungos dimórficos Coccidioides posadasii e Histoplasma capsulatum var. capsulatum : caracterização laboratorial com ênfase no perfil de sensibilidade ao sesquiterpeno farnesol, in vitro - Lima, Rita Amanda Chaves de (2013)
Dimorphic fungi Coccidioides spp. and Histoplasma capsulatum var. capsulatum are the causative agents of coccidioidomycosis and histoplasmosis, respectively, being able to affect humans and other animals. The population genetics of H. capsulatum var. capsulatum ha ve been characterized worldwide. However, there are few studies of g enetic variability for Coccidioides spp., especially in isolates from Brazil. In general, antifungal therapy is effective against these mycoses, although in chronic or disseminated cases , the treatment is often prolonged and difficult to tolerate. Moreover , recurrence and refractory cases have been reported. Recently, it was demonstrated that H. capsulatum is able t o form biofilm. Little is known about the role of this mechanism in the pathogenesis of histoplasmosis and no report on the antifungal susceptib ility of H. capsulatum in biofilm was described to date. In search for new compounds with antifungal activity, the sesquiterpene farnesol has gained prominence for their inhibitory effect on the growth of bacteria and fungi. Considering the above, this stu dy aimed to perform molecular characterization of Brazilian isolates of C. posadasii , as well as, to determine the in vitro effect of farnesol against dimorphic fungi C. posadasii and H . capsulatum var . capsulatum , assessing its effect on fungal growth, sensitivity to antifungal agents, cell permeability, production of ergosterol and in biofilm growth. Thus, strains of C. posadasii were evaluat ed using the techniques of RAPD, M13 - fingerprinting . M acrodilution method was used to determine the min imum inhibitory concentration ( MIC) of farnesol alone and in combination with antifungals . C. posadasii was also subjected to quantification of ergosterol after exposure to sub - inhibitory concentrations of farnesol. In addition , farnesol activity against C. posadasii was also evaluated in the presence of osmotic stress induced by the addition of NaCl to the culture medium during the susceptibility test. Finally, H. capsulatum strains were evaluated in filamentous and yeast phase by microdilution method with farnesol alone and in combination with antifungals. The antifungal susceptibility of these drugs was also evaluated against H. capsulatum in a biofilm. The results of RAPD and M13 - fingerprinting showed similar electrophoretic profiles, showing few polymorphism s among the isolates . F arnesol exhibited low MIC values , ranging from 0.0078 to 0.0616 μ M for C. posadasii and 0.0078 to 0.0312 μM for H. capsulatum . Combinati ons of farnesol with antifungal showed synergistic effects (FIC I ≤ 0.5) in both species Quantification of ergosterol showed that exposure to sub - inhibitory concentrations of farnesol decreased the amount of ergosterol extracted from fungal cells and MIC's lower been found to farnesol when the strains were subjected to osmotic stress, indicating that this compound acts on the membrane fungal . Combinations of farnesol with itraconazole and amphotericin B showed the highest reduction percentages of fungal growth in biofilm . In conclusion, farnesol drug showed promising r esults as antifungal agent against C. posadasii and H. capsulatum , presenting adjuvant action and increasing sensitivity to antifungal agents in vitro . Furthermore, this study contributes to the characterization of the sensitivity profile of the biofilm of H. capsulatum in vitro as well as for genetic characterization of isolates of C. posadasii from Brazil